(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article analyzes the linguocultural features of the the notion of concept “beauty” in three languages. Although it has been studied to a certain extent in world linguistics, there is a need for research related to their study based on the anthropocentric paradigm. In particular, today cultural language concepts have become the object of research of many world linguists. Nevertheless, the need for cross-research of the concept of "beauty" and related linguistic-cultural, linguistic-cognitive features is growing. This research is of special importance because it is directed to solving these important problems. The results obtained can serve as a reliable basis for future researches in this field.